Students’ Metacognitive Reading Strategies in Analyzing Health Analyst Reading Text at First Semester of Bina Mandiri University Gorontalo - Ashrafiany, Ashrafiany (Journal of English Language and Education, 2025)
The research investigates metacognitive reading strategies that use by health analyst students’ when reading health analyst text which containing technical vocabulary and sophisticated conceptual elements. The participants of this research are health analyst students’ who learned English for Health Analyst at first semester. They are 30 students of one classroom. This research investigated successful learner approaches by combining interviews with health analyst students with classroom observation and document. Students use various strategies to grasp health analyst material by metacognitive process such as planning (pre reading), monitoring (while reading) and evaluating (post-reading). The findings of this research where fifteen students were used pre reading, like systematic terminology, ten students were used contextual comprehension in while reading and five students were used Collaborative and contextual comprehension in post reading.